Developing a corporate social responsibility framework for sustainable construction using partial least squares structural equation modeling - Wang, Liang; Zhang, Ping; Ma, Li; Cong, Xuhui; Skibniewski, Miroslaw J. (Technological and Economic Development of Economy, 2020)
Sustainable construction is vital for the embodiment of sustainable development, and corporate social responsibility practice is critical for construction firms to realize sustainable construction. However, the link between sustainable construction and corporate social responsibility is still in its infancy, and previous studies have not developed comprehensive methods for evaluating sustainable construction performance. We first established a conceptual corporate social responsibility framework based on the five aspects of sustainable construction: economic, environmental, social, stakeholders, and health and safety. Then, a set of criteria assessing sustainable construction performance was identified through a literature review and interviews with industry practitioners. A questionnaire survey was conducted to collect primary data and identify the significance of the proposed criteria. Furthermore, partial least squares structural equation modeling (PLS-SEM) was used to statistically validate the conceptual model and identify key factors for sustainable construction. The results revealed that health and safety, and environment are the key aspects, while site inspection and audits, providing a healthy and safe working environment, effective emergency management procedures and safety supervision, compliance with environmental laws and regulations, reducing pollution and waste, and corporate environmental management system are critical to achieving sustainable construction. Our study underlines the link between sustainable construction and corporate social responsibility, improves the evaluation accuracy, and provides new guidelines for practical applications.